Time Traveling Dogs (and Other Native Feminist Ways to Defy Dislocations). (February 2017) - Morrill, Angie
In this article, I analyze a painting by Modoc/Klamath artist Peggy Ball through a Native feminist reading methodology. The painting, Vanport, is named after a city that disappeared in a flood in 1948. The artist survived that flood, and displacement as did thousands of others. The painting is a rememory map of dislocations and hauntings and disappearances. The painting remaps gentrified dislocations, telling stories that focus on the relationship of the present to the past and the past to the future. The painting itself is a Native feminist practice. The travel to places gone, to places that will reappear again; by people gone as well as by people presently alive; into times that existed, that never existed, that will exist again; to times made contemporaneous by time traveling dogs; with people co-present through desire—at the heart of all this time travel is recognition and survivance.